2021
DOI: 10.1139/bcb-2020-0561
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin-d protects against liver fibrosis by regulating the estrogen receptor-β/NLRP3 inflammasome pathway

Abstract: Liver fibrosis is the ultimate common pathway in most types of chronic liver damage characterized by imbalance of extracellular matrix degradation and synthesis. Saikosaponin-d (SSd) possesses anti-inflammatory and anti-liver fibrosis effects. However, the underlying mechanism of SSd in repressing hepatic stellate cells (HSCs) activation remains unclear. Here we found that SSd alleviated remarkably carbon tetrachloride (CCl4)-induced liver fibrosis, as evidenced by decreased collagen level and profibrotic mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…ERβ activation by genistein (a natural phytoestrogen) improves hepatic lipid metabolism ( 264 ). ERβ is involved in the regulation of hepatic fibrosis ( 265 ). The anti-fibrotic effect of estrogen is mediated by ERβ but not by ERα or GPER1.…”
Section: Ers In the Manifestation Of Diseasesmentioning
confidence: 99%
“…ERβ activation by genistein (a natural phytoestrogen) improves hepatic lipid metabolism ( 264 ). ERβ is involved in the regulation of hepatic fibrosis ( 265 ). The anti-fibrotic effect of estrogen is mediated by ERβ but not by ERα or GPER1.…”
Section: Ers In the Manifestation Of Diseasesmentioning
confidence: 99%
“…HF is a diffuse injury to hepatocytes accompanied by inflammation caused by various pathogenic factors. The central link to its occurrence is the excessive deposition of collagen-based extracellular matrix caused by the activation and proliferation of static HSCs ( Kong et al, 2020 ; Lin et al, 2021 ). Studies have confirmed that HF is reversible in the early stages; therefore, it is extremely important to prevent or slow down the occurrence and development of hepatic fibrosis ( Campana and Iredale 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the SSd group was administered SSd (2 mg/kg; Sigma-Aldrich) in saline by oral gavage once a day for 8 weeks. SSd is a potential molecule for treating liver fibrosis and is a liver protectant in a mouse model [ 113 , 114 , 115 ]. In our preliminary studies, serum ALT and AST levels after 1 mg/kg of SSd did not differ significantly from those in the TAA group ( Figure S7 ).…”
Section: Methodsmentioning
confidence: 99%